KEJADIAN PERITONITIS PADA PASIEN CONTINUOUS AMBULATORY PERITONEAL DIALYSIS: IDENTIFIKASI MIKROORGANISME DAN SENSITIFITAS ANTIBIOTIK - Haryanti, Elizabeth; Kandarini, Yenny; Widiana, I Gde Raka; Sudhana, Wayan; Loekman, Jod; Suwitra, Ketut (journal of internal medicine, 2010)
Patients treated with Continuous Ambulatory Peritoneal Dialysis (CAPD) are constantly exposed to microbial invasionof the peritoneal cavity and rapid microbiological diagnosis of peritonitis is essential due to Hospitalization and imposes asignicant burden of morbidity. The aims of this study were to enumerate the association between microorganisms, sensitity,and resistence of antibiotic on CAPD patients with clinical peritonitis.We collected data through medical records by the number of CAPD patients with clinical peritonitis from June 2004 untilJune 2009. The study was analysis with one-way ANOVA. We found 23 patients clinical peritonitis out of 77 CAPD patients,with insidence was 14% per-year, aged 14 ? 65 y (15M; 8F). The chronic pyelonephritic was a leading (16/23) cause of endstages renal disease. Each patients underwent HD prior (5 ? 60 months) to CAPD, with survival time was 2 ? 51 months. Out of23 patients, 4 were returned to hemodialisis, 15 were died, due to cardiogenic shock 46.7%. Aseptic peritonitis was 31.3%, andthe common microorganism was staphylococcus 18.8%. Peritoneal !uid test showed mean score of sensitivity were tetracycline22.93, cipro!oxacin 19.36, piperacillin-tazobactam 17.36, thrimetropin/sulfamethoxazole 16.5, fosfomycin 15.78, consecutivelyand the rest were resistent. Staphylococus was strongly related to insidence peritonitis, and tetracycline was the most highlysensitive antibiotic in CAPD patients.